2021
DOI: 10.21203/rs.3.rs-503988/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Current Status of Newborn Screening for Pompe Disease in Japan

Abstract: Background: Pompe disease is an autosomal recessive inherited metabolic disorder caused by a deficiency of the acid α-glucosidase (AαGlu). Pompe disease manifests as an accumulation of lysosomal glycogen in the skeletal and heart muscle. We conducted newborn screening (NBS) for Pompe disease in Japan from April 2013 to October 2020 to determine the feasibility and utility of NBS for Pompe disease.Results: From the 296,759 newborns whose enzyme activity was measured, 107 of which underwent GAA analysis, we foun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 18 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…A detailed review by Sawada et al 24 provides further detailed information about global PD NBS programs. Patient 1 in this report is the first Japanese IOPD case detected by an NBS program that screened 296 759 newborns from April 2013 to October 2020, 13 which indicates that the incidence of IOPD in Japan is comparable to that in the USA, but is much lower than in Taiwan and some European countries.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…A detailed review by Sawada et al 24 provides further detailed information about global PD NBS programs. Patient 1 in this report is the first Japanese IOPD case detected by an NBS program that screened 296 759 newborns from April 2013 to October 2020, 13 which indicates that the incidence of IOPD in Japan is comparable to that in the USA, but is much lower than in Taiwan and some European countries.…”
Section: Discussionmentioning
confidence: 65%
“…Fukuhara et al 15 reported 28 variants in 38 patients, among which four variants (R40X, Q57X, R608X, Y609X) are listed as possible CRIM-negative in the Pompe disease GAA variant database. 41 Next, Sawada et al 13 reported 29 disease-associated and 14 probably-damaging variants in 296 759 newborns screened for PD, among which only two variants (Y685X and R854X) are associated with CRIM-negative status. 41 All patients detected by NBS in their study had at least one CRIM-positive variant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations